"Their corpses will reach the base of heaven": a third-millennium BC war memorial in northern Mesopotamia?. (August 2021) - Porter, Anne; McClellan, Thomas; Wilhelm, Susanne; Weber, Jill; Baldwin, Alexandra; Colley, Jean; Enriquez, Brittany; Jahrles, Meagan; Lanois, Bridget; Malinov, Vladislav; Ragavan, Sumedh; Robins, Alexandra; et al.
Abstract: Abstract : Burial mounds piled high with enemy corpses are well known in Mesopotamian inscriptions as symbols of victory, but no archaeological examples have so far been recovered. Archaeological investigations of a tall mound adjacent to the site of Tell Banat in Syria have revealed an unusual, late third-millennium BC mortuary population, dominated by adult and sub-adult males. The systematic placement of these human remains and associated assemblages suggests that, rather than containing enemy combatants, this was a memorial to a community's battle dead. The authors propose that the deceased belonged to an organised army, with broader implications for state administration and the adherence or resistance to a new regime fostered by such monumentalisation.